Bonsai Induced Acute Myocardial Infarction: A Case Report - Hüseyin Ayhan; Abdullah Nabi Aslan; Hakan Süygün; Tahir Durmaz (KARE Publishing, 2014)
Incidences of drug abuse and cannabis have increased in young adults, recently. Cannabis induced myocardial infarction has rarely been reported in these people. There is no any literature about a synthetic cannabinoid, being recently most popular Bonsai, to cause myocardial infarction. In this case report we presented a 33 years old male patient who developed acute myocardial infarction after taking high doses of bonsai.